2022
DOI: 10.1128/spectrum.01755-22
|View full text |Cite
|
Sign up to set email alerts
|

The Greenhouse Phyllosphere Microbiome and Associations with Introduced Bumblebees and Predatory Mites

Abstract: Greenhouses, though highly effective agricultural environments, are characterized by reduced sources of bacterial diversity and means of dispersal compared to more natural settings. As it is known that plant health and productivity are affected by associated bacteria, improving our knowledge on the bacterial communities on greenhouse crops is key to further innovate in horticulture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
3
1
Order By: Relevance
“…While low bacterial read numbers were no an issue in the current study, the use of pPNA clamps by Legein and colleagues (2022) did not resolve the issue of low bacterial read numbers i.e., 4,394 and 1,282 for strawberry and tomato leaf phyllospheres, respectively. The same authors revealed that bacterial densities were low at approximately 2 to 3 logs cfu g -1 .…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations
“…While low bacterial read numbers were no an issue in the current study, the use of pPNA clamps by Legein and colleagues (2022) did not resolve the issue of low bacterial read numbers i.e., 4,394 and 1,282 for strawberry and tomato leaf phyllospheres, respectively. The same authors revealed that bacterial densities were low at approximately 2 to 3 logs cfu g -1 .…”
Section: Discussioncontrasting
confidence: 62%
“…However, similar to the observations of Kim and colleagues (2020), utilisation of PNA clamps did increase recovery of usable bacterial sequences by 5,395 reads belonging to the apple flower phytobiome (Steven et al, 2018). In contrast to Legein and colleagues (2022), nearly all non-bacterial reads belonged to plastid DNA whereas very little were mitochondria. Moreover, the most abundant bacterial OTUs were present in both the PNA clamp and control samples, suggesting utilisation of PNA clamps did not result in bias in reads recovered.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations